An unexpected organometallic intermediate in surface-confined Ullmann coupling. Issue 16 (4th April 2019) - Galeotti, Gianluca; Di Giovannantonio, Marco; Cupo, Andrew; Xing, Sarah; Lipton-Duffin, Josh; Ebrahimi, Maryam; Vasseur, Guillaume; Kierren, Bertrand; Fagot-Revurat, Yannick; Tristant, Damien; Meunier, Vincent; Perepichka, Dmitrii F.; et al.
Abstract : Poly( para -phenylene) obtained by a three-step Ullmann coupling: two distinct 1D and 2D organometallic phases are reported. Abstract : Ullmann coupling or, more generally, dehalogenative aryl–aryl coupling, is one of the most widely exploited chemical reactions to obtain one- and two-dimensional polymers on metal surfaces. It is generally described as a two-step reaction: (i) dehalogenation, resulting in the formation of a stable intermediate organometallic phase and subsequent (ii) C–C coupling. The topology of the resulting polymer depends on the number and positions of the halogen atoms in the haloaromatic precursor, although its orientation and order are determined by the structure of the intermediate phase. Hitherto, only one intermediate structure, identified as an organometallic (OM) phase, has been reported for such a reaction. Here we demonstrate the formation of two distinct OM phases during the temperature-induced growth of poly( para -phenylene) from 1, 4-dibromobenzene precursors on Cu(110). Beyond the already known linear-OM chains, we show that a phase reorganization to a chessboard-like 2D-OM can be activated in a well-defined temperature range. This new intermediate phase, revealed only when the reaction is carried out at low molecular coverages, was characterized by X-ray photoelectron spectroscopy, scanning tunneling microscopy and near-edge X-ray absorption fine structure spectroscopy, and modeled by density functional theory calculations. Our data show that the 2D-OM remains stable after cooling down the sample and is stabilized by four-Cu clusters at each node. The observation of such unexpected intermediate phase shows the complexity of the mechanisms underlying on-surface synthesis and broadens the understanding of Ullmann coupling, which continues to be astonishing despite its extensive use.